Histopathology of Cutaneous Leishmaniasis Caused by Leishmania donovani in Sri Lanka. (5th May 2020) - Wijesinghe, Harshima; Gunathilaka, Nayana; Semege, Saveen; Pathirana, Nishantha; Manamperi, Nuwani; de Silva, Chandu; Fernando, Deepika
Abstract : Cutaneous leishmaniasis (CL) is a neglected tropical disease that is gaining importance in Sri Lanka and internationally. The clinical presentation, pathology, and method of parasite elimination in CL vary according to the species. Leishmania donovani is the causative organism for leishmaniasis in Sri Lanka. This collaborative cross-sectional study describes the clinicopathological features of cutaneous leishmaniasis among personnel of the tri-forces serving in the North and East of the country. The histology of fifty cases of CL confirmed by at least two methods (slit skin smear, lesion aspirate, tissue impression, and histology) was reviewed. The parasitic load was assessed semiquantitatively. The histological features were correlated with the clinical presentation and organism load. The majority (89.8%; n = 44 ) presented with a single lesion mostly located in the upper limb (69.4%). The lesion types included papule (34.7%), nodule (32.7%), and an ulcer (30.6%). The evolution time of lesions averaged 31.55 weeks. Epidermal changes were observed in 49 of the biopsies and included hyperkeratosis (90.0%; n = 45 ), acanthosis (44.0%; n = 22 ), atrophy (34.0%; n = 17 ), and interface change (66%; n = 33 ). Dermal changes were seen in all cases and were characterized by a lymphohistioplasmacytic inflammatory infiltrate of variable intensity with ill-formed granuloma in 19 cases (38%) and well-formed epithelioid granulomas in 22 cases (44%). Focal necrosis was present in 20% (n = 10 ). Leishmania amastigote forms were observed in 88% (n = 44 ). Transepidermal elimination (P = 0.025 ), granuloma (P = 0.027 ) formation, and type of lesion (P = 0.034 ) were significantly associated with the organism load. Granuloma formation was associated with a reduction in organism load, indicating that the macrophage activation played an important role in the control of the organism.